Thin film and preparation method thereof, photoelectric device and display device
By using an electric field to fill the metal cations to the inorganic particle gap in the quantum dot light-emitting diode, the stability and photoelectric performance problems caused by surface defects of inorganic particles are solved, and higher density and photoelectric performance improvements are achieved.
Patent Information
- Application Number
- CN202311842593.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2024-12-27
AI Technical Summary
The surface defects of inorganic particles in traditional quantum dot light-emitting diodes lead to poor stability and photoelectric performance of the functional layer, and it is difficult to control the distribution of metal ions by physical mixing method, affecting the luminous efficiency.
By providing a prefabricated film and a metal salt solution, an electric field is applied to allow metal cations to fill the gap between inorganic particles to form a stable film, improve density and stability, and passivate surface defects and suppress leakage current.
It improves the density and photoelectric properties of the film, enhances the luminous efficiency and service life of the optoelectronic devices, and reduces the leakage current phenomenon.
Smart Images

Figure CN119212515A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of display technology, and in particular to a thin film and a preparation method thereof, an optoelectronic device, and a display device. Background Art
[0002] Currently, the widely used optoelectronic devices are organic light-emitting diodes (OLEDs) and quantum dot light-emitting diodes (QLEDs). OLEDs have become the mainstream technology in the field of display technology due to their excellent display performance, such as self-luminescence, simple structure, ultra-thinness, fast response speed, wide viewing angle, low power consumption, and flexible display. QLEDs have the advantages of saturated color and adjustable wavelength of emitted light, and high quantum yield of photoluminescence and electroluminescence, and have become a strong competitor to OLEDs in recent years.
[0003] The structure of traditional OLED and QLED devices generally includes an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer and a cathode. Under the action of the electric field, the holes generated by the anode of the light-emitting diode and the electrons generated by the cathode move and are injected into the hole transport layer and the electron transport layer respectively, and finally migrate to the light-emitting layer. When the two meet in the light-emitting layer, energy excitons are generated, thereby exciting the light-emitting molecules to finally produce visible light. Inorganic particles are often used as materials for the functional layer in QLED. However, inorganic particles have surface defects, resulting in poor stability and photoelectric performance of the functional layer.
[0004] Therefore, the stability of the functional layer needs to be further improved. Summary of the invention
[0005] In view of this, the present application provides a thin film and a preparation method thereof, an optoelectronic device, and a display device.
[0006] The embodiment of the present application is implemented as follows: a photoelectric device includes:
[0007] Providing a prefabricated membrane and a metal salt solution, wherein the metal salt solution includes metal cations, the prefabricated membrane includes inorganic particles, and at least a portion of the prefabricated membrane is in contact with the metal salt solution;
[0008] An electric field is applied to the prefabricated membrane and the metal salt solution to obtain a thin film.
[0009] Correspondingly, an embodiment of the present application further provides a thin film, which is prepared by the above-mentioned preparation method and includes inorganic particles and metal cations filled in the gaps between the inorganic particles.
[0010] Correspondingly, an embodiment of the present application also provides a photoelectric device, comprising a first electrode, a functional layer, and a second electrode stacked in sequence; the functional layer comprises a thin film prepared by the above-mentioned preparation method, or comprises the above-mentioned thin film.
[0011] Correspondingly, an embodiment of the present application further provides a display device, which includes the above-mentioned optoelectronic device.
[0012] The method for preparing the film provided in the present application is conducive to the metal cations filling the gaps between the inorganic particles, stabilizing the film structure, and improving the density and stability of the film. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0014] Figure 1 It is a schematic diagram of the structure of a film prepared by a physical mixing method in the prior art;
[0015] Figure 2 is a flow chart of a method for preparing a thin film provided in an embodiment of the present application;
[0016] Figure 3 is a schematic diagram of the preparation process of the film provided in the embodiment of the present application;
[0017] Figure 4 is a schematic diagram of the structure of the film provided in the embodiment of the present application;
[0018] Figure 5 is a schematic diagram of the structure of the optoelectronic device provided in an embodiment of the present application;
[0019] Figure 6 is a schematic structural diagram of another optoelectronic device provided in an embodiment of the present application;
[0020] Figure 7 is an AFM image of the film provided in Example 1;
[0021] Figure 8 This is an AFM image of the thin film provided in Comparative Example 1.
[0022] Reference numerals:
[0023] Thin film 10; prefabricated film 11; inorganic particles 111; substrate 12; metal cations 13; electric field 14;
[0024] A first electrode 20 ; a second electrode 30 ; a photoactive layer 40 ; a first carrier functional layer 50 ; and a second carrier functional layer 60 . DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0026] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0027] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0028] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or several", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0029] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0030] Doping is an effective method to change the properties of materials. Metal ions such as main group, rare earth or transition metal ions are often doped into quantum dots to effectively regulate the optical, electrical, magnetic and other properties of quantum dots and improve their stability. In some cases, doping quantum dots with metal ions by chemical doping can effectively regulate the photoelectric properties of quantum dots, but it will also bring other additional adverse effects, leading to the complexity of the system. Physical doping of quantum dot films by simple physical mixing methods (such as preparing mixed solutions, etc.) can also regulate the photoelectric properties of quantum dot films, but it is difficult to control the distribution state of the doping elements.
[0031] A large number of studies have shown that the charge injection behavior in quantum dot luminescent film layers is different from that in bulk heterojunction luminescent layers in traditional light-emitting devices. In quantum dot film layers, charges are independently injected into individual quantum dots to form excitons and emit light through radiative recombination. More importantly, charges are transferred between different quantum dots to achieve luminescence of the entire quantum dot layer. Therefore, close contact between quantum dots is conducive to improving the efficiency of charge transfer between different quantum dots, thereby improving luminescence performance. See Figure 1 When the metal cations 13 are doped into the inorganic particles 111 thin film 10 by a simple physical mixing method, they often exist in a disordered and random distribution state. In the doped thin film 10, they are often excessively filled between the inorganic particles 111, resulting in an increase in the distance between the inorganic particles 111, and the inorganic particles 111 cannot directly contact each other, forming a charge transfer barrier between the inorganic particles 111, thereby reducing the luminous efficiency. At the same time, this method, when processing the inorganic particle 111 mixed solution, will cause the metal ions to precipitate at the interface between the inorganic particles 111 and the charge functional layer, resulting in a larger charge injection barrier and reducing the luminous performance.
[0032] The technical solution of this application is as follows:
[0033] First, see Figure 2 and Figure 3 The present invention provides a method for preparing a thin film 10, comprising:
[0034] S11, providing a prefabricated film 11 and a metal salt solution, wherein the metal salt solution includes metal cations 13, and the prefabricated film 11 includes inorganic particles 111, and at least a portion of the prefabricated film 11 is in contact with the metal salt solution;
[0035] S12 , applying an electric field 14 to the prefabricated film 11 and the metal salt solution to obtain a thin film 10 .
[0036] It should be noted that the prefabricated film 11 includes inorganic particles 111 , and there are gaps between the inorganic particles 111 .
[0037] It should also be noted that part of the prefabricated membrane 11 may be located in the metal salt solution so that part of the prefabricated membrane 11 is in contact with the metal salt solution, or the entire prefabricated membrane 11 may be located in the metal salt solution so that the entire prefabricated membrane 11 is in contact with the metal salt solution.
[0038] In the preparation method of the film 10 provided in the present application, under the action of the electric field 14, the metal cations 13 in the metal salt solution continuously enter the film 10 through the gaps between the films 10, and fill the gaps between the inorganic particles 111 and the inorganic particles 111; since the inorganic particles 111 in the film 10 are already in close contact, the metal cations 13 will only fill the gaps without destroying the contact between the original inorganic particles 111, and the metal cations 13 will not form an over-enriched metal cation 13 barrier layer. With the assistance of the electric field 14, the metal cations 13 will fill the gaps, stabilize the structure of the film 10, improve the compactness and stability of the film 10, and inhibit the mutual diffusion of elements when the film 10 contacts other film layers; the metal cations 13 can passivate the surface defects of the inorganic particles 111, reduce the defect density, and improve the photoelectric performance of the film 10; in addition, the metal cations 13 are filled in the gaps, which can prevent the leakage path of holes or electrons, inhibit the generation of leakage current, and further improve the performance of the photoelectric device prepared by the film 10.
[0039] It should be noted that the metal cations 13 enter the gaps between the inorganic particles 111 under the action of the electric field 14, and the positively charged uncoordinated or unbonded metals or ligands in the inorganic particles 111 can enter the solution, and the two exchange to achieve electrical balance.
[0040] It is understandable that a small amount of acidic liquid, alkaline liquid or water can be introduced into the metal salt solution. If there are too few positively charged uncoordinated or unbonded elements in the inorganic particles 111, the acidic liquid, alkaline liquid or water can decompose to ensure electrical balance.
[0041] In some embodiments, the metal cation 13 includes one or more of alkali metal ions, alkaline earth metal ions, transition metal ions, and lanthanide metal ions.
[0042] Furthermore, the alkali metal ions include one or more of lithium ions, sodium ions, potassium ions, rubidium ions, and cesium ions.
[0043] The alkaline earth metal ions include one or more of beryllium ions, magnesium ions, calcium ions, strontium ions, and barium ions.
[0044] The transition metal ions include one or more of scandium ions, titanium ions, vanadium ions, chromium ions, manganese ions, iron ions, cobalt ions, nickel ions, copper ions, zinc ions, yttrium ions, zirconium ions, niobium ions, molybdenum ions, technetium ions, ruthenium ions, rhodium ions, palladium ions, silver ions, cadmium ions, hafnium ions, tantalum ions, tungsten ions, rhenium ions, osmium ions, iridium ions, and platinum ions.
[0045] The lanthanide metal ions include one or more of lanthanum ions, cerium ions, praseodymium ions, neodymium ions, samarium ions, europium ions, gadolinium ions, terbium ions, dysprosium ions, holmium ions, erbium ions, thulium ions, ytterbium ions, and lutetium ions.
[0046] In some embodiments, the metal salt solution also includes anions, and the anions include one or more of acetate ions, sulfate ions, halide ions, aminosulfonate ions, hydroxide ions, carbonyl ions, nitrate ions, tetrahydrate acetate ions, carbonate ions, sulfite ions, silicate ions, thiocyanate ions, cyanide ions, and phosphate ions.
[0047] Preferably, the metal cations in the metal salt solution include one or more of lithium ions, sodium ions, potassium ions, rubidium ions, cesium ions, magnesium ions, calcium ions, strontium ions, barium ions, titanium ions, vanadium ions, chromium ions, manganese ions, iron ions, cobalt ions, nickel ions, copper ions, zinc ions, yttrium ions, zirconium ions, molybdenum ions, silver ions, and cadmium ions.
[0048] The anions in the metal salt solution include one or more of fluoride ions, iodide ions, acetate ions, sulfate ions, chloride ions, hydroxide ions, carbonyl ions, nitrate ions, tetrahydrate acetate ions, carbonate ions, sulfite ions, thiocyanate ions, cyanide ions, and phosphate ions.
[0049] The metal salt in the metal salt solution includes NaI, KF, KIO3, Na2B4O7·10H2O, CH3COOLi, CH3COONa, CH3COOK, (CH3COO)2Mg, LiSO4, Na2SO4, K2SO4, MgSO4, CaSO4, (CH3COO)4Ti, (CH3COO)3V, (CH3COO)3Cr, (CH3COO)3Fe, (CH3COO)2Co, (CH3COO)2Ni, (CH3COO)2Cu, (CH3COO)2Zn, (CH3COO)2Mo, CH3COOAg, (CH3COO)2Cd, Ti(SO4)2, V2(SO4)3, Cr2(SO4), Fe 2(SO4)3, CoSO4, NiSO4, CuSO4·5H2O, ZnSO4·7H2O, MoSO4·xH2O, Ag2SO4, CdSO4·xH2O, LiCl, NaCl, KCl, TiCl4, VCl3, CrCl3·6H2O, FeCl3·6H2O, CoCl2·6H2O, NiCl2·6H2O, CuCl2·2H2O, ZnCl2, ZrCl4·xH2O, MoCl5·xH2O, AgCl, CdCl2·2H2O, (COOH)3Al·xH2O, (COOH)3Ga·xH2O, (COOH)2Cu·xH2O, (COOH)2Zn·xH2O, LiNO3, one or more thereof.
[0050] In some embodiments, in the metal salt solution, the mass concentration of the metal cation 13 is 0.1 mg / mL to 500 mg / mL, for example, 10 mg / mL, 20 mg / mL, 50 mg / mL, 100 mg / mL, 200 mg / mL, 300 mg / mL, 400 mg / mL, etc.
[0051] In some embodiments, the metal salt solution further includes a first solvent.
[0052] Furthermore, the first solvent includes one or more of deionized water, chlorobenzene, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide, acetone, acetophenone, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, ethyl ester, pyrrole, butyric acid, and cresol.
[0053] In some embodiments, the preparation method further includes providing a substrate 12, the prefabricated film 11 is disposed on the substrate 12, and the direction of the electric field 14 is the thickness direction from the prefabricated film 11 to the substrate 12. In other words, the negative pole of the electric field 14 is located on the side of the substrate 12 away from the prefabricated film 11.
[0054] In some embodiments, the substrate 12 includes a device preform, a substrate, a metal plate, or a container bottom.
[0055] It can be understood that the substrate 12 can play a role in supporting the prefabricated film 11, preventing the metal cations 13 from passing through the prefabricated film 11 to reach the negative electrode of the electric field 14 when the prefabricated film 11 is located in the middle of the electric field 14 under the action of the electric field 14. The device preform is a device preform for preparing a photoelectric device, which may include an electrode, or may include a stacked electrode and a carrier functional layer, and a photoactive layer 40. The substrate may be a conventional substrate in the art; the metal plate is the negative plate of the electric field 14, and the electric field 14 is defined by the positive plate and the negative plate arranged oppositely, and the negative plate can prevent the metal cations 13 from passing through the film 10; when the metal salt solution is in a container, such as a beaker, the film 10 sinks to the bottom of the glass due to gravity, and the negative electrode is connected to the bottom of the glass, and at this time the bottom of the glass supports the film 10.
[0056] In some embodiments, the substrate may be a rigid substrate or a flexible substrate. Further, the material of the substrate may be selected from but not limited to at least one of glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide and polyether sulfone.
[0057] In some embodiments, the prefabricated film 11 has a thickness of 1 nm to 200 nm, for example, 20 nm, 50 nm, 100 nm, 120 nm, 150 nm, 180 nm, etc.
[0058] In some embodiments, the average particle size of the inorganic particles 111 is 1 nm to 50 nm, for example, 2 nm, 3 nm, 4 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, etc.
[0059] In some embodiments, the inorganic particles 111 include one or more of quantum dots, N-type semiconductor particles, and P-type semiconductor particles.
[0060] In some embodiments, the quantum dots may be selected from, but not limited to, one or more of, single structure quantum dots, core-shell structure quantum dots, and perovskite quantum dots.
[0061] The material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot can be selected from, but not limited to, one or more of the group II-VI compounds, group IV-VI compounds, group III-V compounds and group I-III-VI compounds. The shell of the core-shell structure quantum dot is one or more layers. The II-VI group compound can be selected from but not limited to one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe. The IV-VI group compound can be selected from but not limited to one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The III-V group compound may be selected from, but not limited to, one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, and InAlPSb. The I-III-VI group compound may be selected from, but not limited to, one or more of CuInS2, CuInSe2, and AgInS2.
[0062] As an example, the core-shell structure quantum dots can be selected from but not limited to one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS. The “ / ” in the above expressions such as CdSe / ZnS means that the substance after the “ / ” (as a shell layer) covers the substance before the “ / ” (as a core layer).
[0063] The general structural formula of the perovskite quantum dot is AMX3, wherein A is selected from Cs + 、CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is selected from Cl - Br - ,I - One or more of the .
[0064] In some embodiments, the N-type semiconductor particles include one or more of a first doped metal oxide particle, a first undoped metal oxide particle, a IIB-VIA semiconductor material, a IIIA-VA semiconductor material, and an IB-IIIA-VIA semiconductor material. The material of the first undoped metal oxide particle includes one or more of ZnO, TiO2, SnO2, ZrO2, and Ta2O5. The metal oxide in the first doped metal oxide particle includes one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and Al2O3. The doping element in the first doped metal oxide particle includes one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga. The IIB-VIA semiconductor material includes one or more of ZnS, ZnSe, and CdS. The IIIA-VA semiconductor material includes one or more of InP and GaP. The IB-IIIA-VIA semiconductor material includes one or more of CuInS and CuGaS.
[0065] In some embodiments, the P-type semiconductor particles include one or more of a second doped metal oxide particle, a second undoped metal oxide particle, a metal sulfide, a metal selenide and a metal nitride, the metal oxide in the second doped metal oxide particle and the metal oxide in the second undoped metal oxide particle each independently include one or more of MoO3, WO3, NiO, CrO3, CuO, V2O5, the doping element in the second doped metal oxide particle includes one or more of Mo, W, Ni, Cr, Cu, V, the metal sulfide includes one or more of CuS, MoS3, WS3, the metal selenide includes one or more of MoSe3, WSe3, and the metal nitride includes P-type gallium nitride.
[0066] In S12:
[0067] In some embodiments, the electric field is a direct current electric field.
[0068] In some embodiments, the strength of the electric field 14 is 10 4 V / m~10 8 V / m, for example, can be 5×10 4 V / m, 10 5 V / m, 5×10 5 V / m, 10 6 V / m, 5×10 6 V / m, 10 7 V / m, 5×10 7 V / m, etc.
[0069] In some embodiments, the time for applying the electric field 14 is 0.1 min to 60 min, for example, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, etc.
[0070] In this way, within the intensity of the electric field 14 and the application range of the electric field 14 , the metal cations 13 are facilitated to move toward the negative pole of the electric field 14 and fill the gaps between the inorganic particles 111 .
[0071] In some embodiments, the film 10 is doped with the metal cations 13; the preparation method further comprises: washing the film 10 in a second solvent. It is understood that after the second solvent washing treatment, the residues on the surface of the film 10 can be removed, and the residues include impurities such as metal salts, free or uncoordinated metal ions and anions. When a small amount of acidic liquid, alkaline liquid or water is introduced, the impurities also include such substances.
[0072] In some embodiments, the film 10 is placed in the second solvent for washing for 1 second to 600 seconds, for example, 50 seconds, 100 seconds, 150 seconds, 200 seconds, 250 seconds, 300 seconds, 350 seconds, 400 seconds, 450 seconds, 500 seconds, 550 seconds, etc.
[0073] In some embodiments, the second solvent includes one or more of deionized water, chlorobenzene, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide, acetone, acetophenone, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, ethyl ester, pyrrole, butyric acid, and cresol.
[0074] In some embodiments, the film 10 is further heated after being washed. It is understood that the heating can also be performed after the film 10 is washed in the second solvent.
[0075] Further, in some embodiments, the heating temperature is 60°C to 230°C, for example, 80°C, 100°C, 120°C, 150°C, 180°C, 200°C, 220°C, etc.
[0076] In some embodiments, the heating time is 1 min to 120 min, for example, 10 min, 20 min, 40 min, 50 min, 60 min, 80 min, 100 min, etc.
[0077] In this way, under the above-mentioned heating conditions, it is beneficial to further remove the residual solvent and drive the metal cations 13 to move, thereby forming a stable film 10.
[0078] Second, see Figure 4 The embodiment of the present application also provides a film 10, which is prepared by the above preparation method.
[0079] In some embodiments, the thin film 10 includes inorganic particles 111 and metal cations 13 disposed in gaps between the inorganic particles 111 .
[0080] In some embodiments, the metal cation 13 is connected to the surface of the inorganic particle 111 , and the connection bond between the inorganic particle 111 and the metal cation 13 includes one or more of an ionic bond, a covalent bond, and a metallic bond.
[0081] Specifically, there are some dangling bonds on the surface of the inorganic particles 111, and the metal cations 13 can be combined with the dangling bonds on the surface of the inorganic particles 111 through ionic bonds, covalent bonds, and metallic bonds. It should be noted that ionic bonds are chemical bonds formed between anions and cations through electrostatic interactions; covalent bonds are interactions between atoms through shared electron pairs; and metallic bonds are electrostatic attractions between free electrons and metal ions arranged in a lattice.
[0082] In some embodiments, the roughness of the film is 0.3 nm to 1.32 nm, for example, 0.4 nm, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1 nm, 1.1 nm, 1.2 nm, 1.3 nm, etc. Within the roughness range, leakage current of the film is reduced.
[0083] In some embodiments, in the film 10, the molar ratio of the metal cations 13 to the inorganic particles 111 is (1-100):1, for example, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, etc.
[0084] Third, see Figure 5 The embodiment of the present application further provides a photoelectric device, comprising a first electrode 20, a functional layer and a second electrode 30 stacked in sequence; the functional layer comprises a thin film 10 prepared by the above-mentioned preparation method.
[0085] In the optoelectronic device provided in the present application, the metal cations 13 are filled in the gaps between the inorganic particles 111, which can prevent the leakage paths of holes or electrons, inhibit the generation of leakage current, and further improve the optoelectronic performance of the optoelectronic device.
[0086] In some embodiments, the optoelectronic device comprises a light emitting diode.
[0087] In some embodiments, see Figure 6 , the functional layer includes one or more of a first carrier functional layer 50, a photoactive layer 40, and a second carrier functional layer 60; the first carrier functional layer 50 is arranged between the first electrode 20 and the photoactive layer 40, and the second carrier functional layer 60 is arranged between the photoactive layer 40 and the second electrode 30; one or more of the first carrier functional layer 50, the photoactive layer 40, and the second carrier functional layer 60 includes the thin film 10 obtained by the above preparation method.
[0088] In some embodiments, the first carrier functional layer 50 is a hole functional layer, and the second carrier functional layer 60 is an electron functional layer. Accordingly, the first electrode 20 is an anode, and the second electrode 30 is a cathode.
[0089] In some other embodiments, the second carrier functional layer 60 is a hole functional layer, and the first carrier functional layer 50 is an electron functional layer. Accordingly, the second electrode 30 is an anode, and the first electrode 20 is a cathode.
[0090] Furthermore, the hole functional layer includes one or more of a hole injection layer and a hole transport layer.
[0091] The electronic functional layer includes one or more of an electron injection layer and an electron transport layer.
[0092] In some embodiments, the first electrode 20 and the second electrode 30 each independently include one or more of a metal, a carbon material and a metal oxide; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode in which a metal is arranged between doped or undoped transparent metal oxides, and the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, MoO3 and AMO, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2. Here, “ / ” represents a stacked structure. For example, AZO / Ag / AZO represents a composite electrode including an AZO layer, an Ag layer and an AZO layer stacked in sequence.
[0093] One or more of the photoactive layer 40 , the hole functional layer and the electron functional layer include metal cations 13 .
[0094] It can be understood that when the photoactive layer 40 is prepared by the above preparation method, the material of the photoactive layer 40 includes quantum dots and metal cations 13 .
[0095] In some embodiments, when the photoactive layer 40 is not prepared by the above-mentioned preparation method, the material of the photoactive layer 40 includes a luminescent material, and the luminescent material includes one or more of an organic luminescent material and a quantum dot; the organic luminescent material includes 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine iridium(III)], 4,4',4"-tri(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine iridium], diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials. One or more of the following: optical materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF materials, polymers containing BN covalent bonding, HLCT materials, and Exciplex luminescent materials; the quantum dots include one or more of single-structure quantum dots, core-shell structure quantum dots, and perovskite-type semiconductor materials, and the materials of the single-structure quantum dots, the core materials of the core-shell structure quantum dots, and the shell materials of the core-shell structure quantum dots are independently selected from II-VI group compounds, IV-VI group compounds, III-V group compounds, and I-III-VI group compounds. One or more of the following: the shell layer of the core-shell structure quantum dot is one or more layers; the II-VI group compound includes CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS , CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound includes one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe;The III-V group compounds include one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compounds include one or more of CuInS2, CuInSe2 and AgInS2; the general structural formula of the perovskite semiconductor material is AMY3, wherein A is Cs; + 、CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, Y is selected from Cl - Br - ,I - One or more of the .
[0096] It can be understood that when the electronic functional layer is prepared by the above preparation method, the material of the electronic functional layer includes N-type semiconductor particles and metal cations 13 .
[0097] In some embodiments, when the electronic functional layer is not prepared by the above-mentioned preparation method, the material of the electronic functional layer includes electronic functional materials, and the electronic functional materials include first doped metal oxide particles, first undoped metal oxide particles, IIB-VIA semiconductor materials, IIIA-VA semiconductor materials and IB-IIIA-VIA semiconductor materials. One or more of the materials of the first undoped metal oxide particles include ZnO, TiO2, SnO2, ZrO2, Ta2O5, and the metal oxide in the first doped metal oxide particles includes The doping elements in the first doped metal oxide particles include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga. The IIB-VIA semiconductor materials include one or more of ZnS, ZnSe, and CdS. The IIIA-VA semiconductor materials include one or more of InP and GaP. The IB-IIIA-VIA semiconductor materials include one or more of CuInS and CuGaS.
[0098] It can be understood that when the hole functional layer is prepared by the above preparation method, the material of the hole functional layer includes P-type semiconductor particles and metal cations 13.
[0099] In some embodiments, when the hole functional layer is not prepared by the above preparation method, the material of the hole functional layer includes a hole functional material, and the hole functional material includes 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis( phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazol-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[( 9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylenevinylene), poly(phenylenevinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylenevinylene] [vinyl], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraaryl benzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, second doped metal oxide particles, second undoped metal oxide particles, metal sulfide, metal selenide and metal nitride, the metal oxide in the second doped metal oxide particles and the metal oxide in the second undoped metal oxide particles independently include one or more of MoO3, WO3, NiO, CrO3, CuO, V2O5, the doping element in the second doped metal oxide particles includes one or more of Mo, W, Ni, Cr, Cu, V, the metal sulfide includes one or more of CuS, MoS3, WS3, the metal selenide includes one or more of MoSe3, WSe3, and the metal nitride includes P-type gallium nitride. ,
[0100] In a fourth aspect, an embodiment of the present application further provides a display device, which includes the above-mentioned optoelectronic device.
[0101] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.
[0102] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0103] Example 1
[0104] This embodiment provides a thin film, including CdSeS quantum dots and zinc ions filled in the gaps between the CdSeS quantum dots; the preparation method thereof is as follows:
[0105] Providing a substrate, spin-coating a 40 mg / mL CdSeS quantum dot solution on the substrate, and then annealing the substrate on a hot plate at 100° C. for 15 min to form a quantum dot pre-film with a thickness of 30 nm;
[0106] A zinc acetate dimethyl sulfoxide solution with a mass concentration of 20 mg / mL is provided, and a substrate and a quantum dot prefabricated film are placed in the zinc acetate solution. A negative electrode of a power supply is connected to the side of the substrate away from the quantum dot prefabricated film, and a positive electrode of a power supply is connected to the side of the zinc acetate solution away from the substrate. A 4x10 5V / m electric field and maintain it for 2 min to move zinc ions into the gaps between CdSeS quantum dots in the quantum dot prefabricated film;
[0107] The quantum dot prefabricated film was taken out, placed in a solvent for washing for 300 seconds to remove the surface residue on the quantum dot prefabricated film, and then heated at 100° C. for 60 minutes to obtain a thin film.
[0108] Example 2
[0109] Example 2 is basically the same as Example 1, except that the electric field strength in Example 2 is 10 8 V / m.
[0110] Example 3
[0111] Example 3 is basically the same as Example 1, except that the electric field strength in Example 3 is 10 4 V / m.
[0112] Example 4
[0113] Example 4 is substantially the same as Example 1, except that the electric field is applied for 60 minutes in Example 4.
[0114] Example 5
[0115] Example 5 is substantially the same as Example 1, except that the electric field is applied for 0.1 min in Example 5.
[0116] Example 6
[0117] Example 6 is substantially the same as Example 1, except that the concentration of zinc acetate in Example 6 is 500 mg / mL.
[0118] Example 7
[0119] Example 7 is substantially the same as Example 1, except that the concentration of zinc acetate in Example 7 is 0.1 mg / mL.
[0120] Example 8
[0121] Example 8 is substantially the same as Example 1, except that in Example 8, CdSeS quantum dots are replaced with CdSe / ZnS quantum dots.
[0122] Example 9
[0123] Example 9 is substantially the same as Example 1, except that in Example 9, CdSeS quantum dots are replaced with mixed quantum dots of CdSeS and CdSe / ZnS.
[0124] Example 10
[0125] Example 10 is substantially the same as Example 1, except that in Example 10, zinc acetate is replaced by potassium sulfate.
[0126] Embodiment 11
[0127] Example 11 is substantially the same as Example 1, except that in Example 11, zinc acetate is replaced by a mixed metal salt solution of zinc acetate and potassium sulfate.
[0128] Example 12
[0129] Example 12 is substantially the same as Example 1, except that in Example 12, CdSeS quantum dots are replaced by nickel oxide, and zinc acetate is replaced by magnesium nitrate.
[0130] Example 13
[0131] Example 13 is substantially the same as Example 1, except that in Example 13, CdSeS quantum dots are replaced by zinc oxide, and zinc acetate is replaced by magnesium nitrate.
[0132] Comparative Example 1
[0133] This comparative example provides a thin film, the material of the thin film includes CdSeS quantum dots, and the preparation method refers to the preparation method of the quantum dot prefabricated film in Example 1.
[0134] Comparative Example 2
[0135] This comparative example provides a thin film, and the preparation method includes: mixing a CdSeS quantum dot solution and a zinc acetate solution, and spin coating the mixture on a substrate to obtain a thin film.
[0136] Comparative Example 3
[0137] This comparative example is substantially the same as Example 1, except that in this comparative example, no electric field is applied, and the zinc acetate solution is directly spin-coated on the quantum dot prefabricated film.
[0138] Comparative Example 4
[0139] Comparative Example 4 is substantially the same as Comparative Example 1, except that in Comparative Example 4, the CdSeS quantum dots are replaced with nickel oxide.
[0140] Comparative Example 5
[0141] Comparative Example 5 is substantially the same as Comparative Example 1, except that in Comparative Example 5, CdSeS quantum dots are replaced with zinc oxide.
[0142] The roughness Ra of the films of Examples 1 to 13 and Comparative Examples 1 to 5 was tested by AFM, and the AFM image of Example 1 was obtained as follows: Figure 7 As shown, the AFM image of Comparative Example 1 is as follows Figure 8 The roughness results are shown in Table 1.
[0143] Table 1
[0144]
[0145]
[0146] From Table 1, we can see that:
[0147] The roughness of Examples 1 to 7 and Comparative Example 1 and Figure 7 , Figure 8 It can be obtained that the roughness of the film prepared by the method provided in the present application is less than 1 nm, while the roughness of the film in Comparative Example 1 is 1.67 nm; it indicates that applying an electric field promotes the doping of metal cations in quantum dots, passivates the defects of quantum dots, improves the film forming property of the film, and reduces the roughness of the film; the intensity of the electric field, the treatment time, and the concentration of the metal salt solution have a certain influence on the roughness of the film, but the effect is much better than that of Comparative Example 1;
[0148] It can be seen from Example 1 and Comparative Examples 2 to 3 that the roughness of the quantum dot film obtained by directly mixing the metal salt solution and the quantum dot solution and spin coating the metal salt solution on the quantum dot film is improved compared with the quantum dot film of Comparative Example 1, but its roughness is still higher than that of the film in Example 1;
[0149] It can be seen from Examples 8 to 11 and Comparative Example 1 that the materials and types of replacing the quantum dot materials and metal cations have no significant effect on the roughness of the film, and are all lower than the roughness of the film in Comparative Example 1, indicating that the film prepared by the method provided in the present application has high stability and density.
[0150] It can be seen from Examples 1, 12 to 13 and Comparative Examples 1, 4 to 5 that inorganic particles, whether quantum dots, P-type semiconductor particles, or N-type semiconductor particles, can be doped with metal cations using the method provided in this scheme to effectively reduce the roughness of the film and improve the density of the film.
[0151] Device Example 1
[0152] This embodiment provides a photoelectric device, and the preparation method is as follows:
[0153] Cleaning the substrate with the patterned electrode; treating the surface of the ITO substrate with UV-ozone for 5 minutes to further remove organic matter attached to the surface of the ITO substrate and to increase the work function of the ITO substrate, thereby forming an anode;
[0154] The PEDOT:PSS solution was spin-coated on the ITO substrate and annealed at 150 °C for 30 min to form a hole injection layer with a thickness of 30 nm;
[0155] The TFB solution was spin-coated on the hole injection layer and annealed at 150°C for 20 min to form a hole transport layer with a thickness of 40 nm;
[0156] Prepare a quantum dot light-emitting layer according to the method of Example 1;
[0157] Spin-coat ZnO ethanol dispersion on the quantum dot light-emitting layer and anneal at 80°C for 30 min to form an electron transport layer with a thickness of 30 nm;
[0158] Place it in a vapor deposition chamber and thermally evaporate a layer of silver through a mask plate to form a 100nm cathode;
[0159] Encapsulation is performed to obtain an optoelectronic device.
[0160] Device Examples 2 to 11
[0161] Device Examples 2 to 11 are substantially the same as Device Example 1, with the only difference being that the quantum dot light-emitting layers in Device Examples 2 to 11 are prepared by the methods of Examples 2 to 11, respectively.
[0162] Device Examples 12 to 14
[0163] Device Examples 12 to 14 are substantially the same as Device Example 1, except that:
[0164] The quantum dot light-emitting layer in device embodiment 12 is a quantum dot prefabricated film, and the hole functional layer is prepared by the method of embodiment 12;
[0165] The quantum dot light-emitting layer in device embodiment 13 is a quantum dot prefabricated film, and the electronic functional layer is prepared by the method of embodiment 13;
[0166] In device example 14, the hole functional layer is prepared by the method of example 12; and the electron functional layer is prepared by the method of example 13.
[0167] Device Comparison Examples 1 to 3
[0168] Device Comparative Examples 1 to 3 are substantially the same as Device Example 1, except that the quantum dot light-emitting layers in Device Comparative Examples 1 to 3 are prepared by the methods of Examples 1 to 3, respectively.
[0169] Device Comparison Example 4
[0170] Device Comparative Example 4 is substantially the same as Device Comparative Example 1, except that the hole functional layer in Device Comparative Example 4 is prepared by the method of Example 4.
[0171] The external quantum efficiency EQE and the lifespan T95@1000nit of the electron transport layer of device embodiments 1 to 14 and device comparative examples 1 to 4 were tested respectively, and the results are shown in Table 2.
[0172] Among them, the test method of external quantum efficiency EQE is: the ratio of the number of electron-hole pairs injected into quantum dots to the number of emitted photons, the unit is %, which is an important parameter to measure the quality of electroluminescent devices, and can be obtained by measuring with EQE optical testing instruments. The specific calculation formula is as follows:
[0173]
[0174] Among them, η e is the light output coupling efficiency, η r is the ratio of the number of recombined carriers to the number of injected carriers, χ is the ratio of the number of photon-generating excitons to the total number of excitons, K R is the radiation process rate, K NR is the rate of the non-radiative process.
[0175] Test conditions: carried out at room temperature, air humidity is 30-60%.
[0176] The test method for the life span T95@1000nit is: the time required for the device to reduce its brightness to a certain proportion of the maximum brightness under constant current or voltage driving. The time when the brightness drops to 95% of the maximum brightness is defined as T95, and this life span is the measured life span. In order to shorten the test cycle, the device life span test is usually carried out at high brightness by accelerating device aging, and the life span at high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula. For example, the life span at 1000nit is calculated as T95@1000nit. The specific calculation formula is as follows:
[0177]
[0178] Among them, T95 L For lifespan at low brightness, T95 H is the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, A is the acceleration factor, and this experiment measured the lifespan of several groups of green QLED devices at rated brightness and found that the A value was 1.7.
[0179] Table 2
[0180]
[0181]
[0182] From Table 2, we can see that:
[0183] It can be seen from device embodiments 1 to 7 and device comparative example 1 that the external quantum efficiency of the optoelectronic devices prepared by the method provided in the present application is higher than 20%, while the external quantum efficiency of the optoelectronic device in device comparative example 1 is lower than 20%, and the service life of the optoelectronic devices of device embodiments 1 to 7 is much longer than that of comparative example 1, which indicates that applying an electric field can promote the doping of metal cations in quantum dots, passivate the defects of quantum dots, improve the optoelectronic properties of the light-emitting layer, and inhibit the generation of leakage current; the intensity of the electric field, the treatment time, and the concentration of the metal salt solution have a certain influence on the performance of the optoelectronic device, but the effect is much better than that of device comparative example 1;
[0184] It can be seen from device example 1 and device comparative examples 2 to 3 that the external quantum efficiency of the optoelectronic device of device comparative example 1 is increased by directly mixing the metal salt solution and the quantum dot solution and spin coating the metal salt solution on the quantum dot film, but the service life is still lower than the performance of the optoelectronic device of device example 1; this indicates that ordinary physical mixed doping with metal cations has a certain improvement effect on quantum dots, but it may increase steric hindrance, so that quantum dots cannot be in close contact with each other; spin coating the metal salt solution on the quantum dot film will cause the enrichment of metal cations on the surface of the quantum dot film to be much higher than the gap filling, thereby causing a larger charge injection barrier, and further affecting the optoelectronic performance of the optoelectronic device;
[0185] It can be seen from device embodiments 8 to 11 and device comparison example 1 that replacing the materials and types of quantum dot materials and metal cations has no significant effect on the external quantum efficiency and service life of the optoelectronic device. The external quantum efficiency is about 30%, and the service life is about 40,000 hours, which is much higher than the performance of the optoelectronic device in device comparison example 1. This shows that the method provided in the present application is widely applicable and can achieve beneficial effects.
[0186] It can be seen from device embodiments 1, 14 to 15 and device comparison examples 1 and 4 that in the functional layer of the optoelectronic device, whether it is a photoactive layer, a hole functional layer, or an electron functional layer, the functional layer is prepared by the method provided in the present scheme and applied to the optoelectronic device, which can effectively improve the external quantum efficiency of the optoelectronic device and extend the service life of the optoelectronic device; among them, the photoactive layer, the hole functional layer, and the electron functional layer in device embodiment 15 are all prepared by the method provided in this application, and have the highest external quantum efficiency and the longest service life.
[0187] The thin film and its preparation method, optoelectronic device, and display device provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A method for preparing a thin film, characterized in that: include: Providing a prefabricated membrane and a metal salt solution, wherein the metal salt solution includes metal cations, the prefabricated membrane includes inorganic particles, and at least a portion of the prefabricated membrane is in contact with the metal salt solution; An electric field is applied to the prefabricated membrane and the metal salt solution to obtain a thin film.
2. The preparation method according to claim 1, characterized in that The strength of the electric field is 10 4 V / m~10 8 V / m; and / or The time of applying the electric field is 0.1min to 60min; and / or The electric field is a direct current electric field.
3. The preparation method according to claim 1, characterized in that: The average particle size of the inorganic particles is 1 nm to 50 nm; and / or The thickness of the prefabricated film is 1 nm to 200 nm; and / or In the metal salt solution, the mass concentration of the metal cation is 0.1 mg / mL to 500 mg / mL.
4. The preparation method according to claim 1, characterized in that: The preparation method further comprises providing a substrate, the prefabricated film is arranged on the substrate, and the direction of the electric field is the thickness direction from the prefabricated film to the substrate; and / or The metal cations include one or more of alkali metal ions, alkaline earth metal ions, transition metal ions, and lanthanide metal ions; and / or The inorganic particles include one or more of quantum dots, N-type semiconductor particles, and P-type semiconductor particles.
5. The preparation method according to claim 4, characterized in that: The substrate includes a device preform, a substrate, a metal plate or a container bottom; and / or The alkali metal ions include one or more of lithium ions, sodium ions, potassium ions, rubidium ions, and cesium ions; and / or The alkaline earth metal ions include one or more of beryllium ions, magnesium ions, calcium ions, strontium ions, and barium ions; and / or The transition metal ions include one or more of scandium ions, titanium ions, vanadium ions, chromium ions, manganese ions, iron ions, cobalt ions, nickel ions, copper ions, zinc ions, yttrium ions, zirconium ions, niobium ions, molybdenum ions, technetium ions, ruthenium ions, rhodium ions, palladium ions, silver ions, cadmium ions, hafnium ions, tantalum ions, tungsten ions, rhenium ions, osmium ions, iridium ions, and platinum ions; and / or The lanthanide metal ions include one or more of lanthanum ions, cerium ions, praseodymium ions, neodymium ions, samarium ions, europium ions, gadolinium ions, terbium ions, dysprosium ions, holmium ions, erbium ions, thulium ions, ytterbium ions, and lutetium ions; and / or The quantum dots include one or more of single-structure quantum dots, core-shell quantum dots and perovskite semiconductor materials. The materials of the single-structure quantum dots, the core materials of the core-shell quantum dots and the shell materials of the core-shell quantum dots are independently selected from one or more of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds. The shell of the core-shell quantum dots is one or more layers. The II-VI compounds include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, CdSeS, CdSeTe, Cd STe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compounds include SnS, SnSe, SnTe, PbS, PbSe, Pb Te, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V group compounds include GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP , InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound includes one or more of CuInS2, CuInSe2 and AgInS2; the general structural formula of the perovskite semiconductor material is AMX3, wherein A is Cs + 、CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is selected from Cl - Br - ,I - One or more of; and / or The N-type semiconductor particles include one or more of a first doped metal oxide particle, a first undoped metal oxide particle, a IIB-VIA semiconductor material, a IIIA-VA semiconductor material, and an IB-IIIA-VIA semiconductor material, the material of the first undoped metal oxide particle includes one or more of ZnO, TiO2, SnO2, ZrO2, and Ta2O5, the metal oxide in the first doped metal oxide particle includes one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and Al2O3, the doping element in the first doped metal oxide particle includes one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga, the IIB-VIA semiconductor material includes one or more of ZnS, ZnSe, and CdS, the IIIA-VA semiconductor material includes one or more of InP and GaP, and the IB-IIIA-VIA semiconductor material includes one or more of CuInS and CuGaS; and / or The P-type semiconductor particles include one or more of a second doped metal oxide particle, a second undoped metal oxide particle, a metal sulfide, a metal selenide and a metal nitride. The metal oxide in the second doped metal oxide particle and the metal oxide in the second undoped metal oxide particle independently include one or more of MoO3, WO3, NiO, CrO3, CuO and V2O5. The doping element in the second doped metal oxide particle includes one or more of Mo, W, Ni, Cr, Cu and V. The metal sulfide includes one or more of CuS, MoS3 and WS3. The metal selenide includes one or more of MoSe3 and WSe3. The metal nitride includes P-type gallium nitride.
6. The preparation method according to claim 1, characterized in that: The metal salt solution also includes anions, and the anions include one or more of acetate ions, sulfate ions, halogen ions, aminosulfonate ions, hydroxide ions, carbonyl ions, nitrate ions, tetrahydrate acetate ions, carbonate ions, sulfite ions, silicate ions, thiocyanate ions, cyanide ions, and phosphate ions; and / or The metal salt solution also includes a first solvent; the first solvent includes one or more of deionized water, chlorobenzene, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide, acetone, acetophenone, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, ethyl ester, pyrrole, butyric acid, and cresol.
7. The preparation method according to claim 1, characterized in that: The metal cations in the metal salt solution include one or more of lithium ions, sodium ions, potassium ions, rubidium ions, cesium ions, magnesium ions, calcium ions, strontium ions, barium ions, titanium ions, vanadium ions, chromium ions, manganese ions, iron ions, cobalt ions, nickel ions, copper ions, zinc ions, yttrium ions, zirconium ions, molybdenum ions, silver ions, and cadmium ions; and / or The anions in the metal salt solution include one or more of fluoride ion, iodide ion, acetate ion, sulfate ion, chloride ion, hydroxide ion, carbonyl ion, nitrate ion, tetrahydrate acetate ion, carbonate ion, sulfite ion, thiocyanate ion, cyanide ion, and phosphate ion; and / or The metal salt in the metal salt solution includes NaI, KF, KIO3, Na2B4O7·10H2O, CH3COOLi, CH3COONa, CH3COOK, (CH3COO)2Mg, LiSO4, Na2SO4, K2SO4, MgSO4, CaSO4, (CH3COO)4Ti, (CH3COO)3V, (CH3COO)3Cr, (CH3COO)3Fe, (CH3COO)2Co, (CH3COO)2Ni, (CH3COO)2Cu, (CH3COO)2Zn, (CH3COO)2Mo, CH3COOAg, (CH3COO)2Cd, Ti(SO4)2, V2(SO4)3, Cr2(SO4), Fe 2(SO4)3, CoSO4, NiSO4, CuSO4·5H2O, ZnSO4·7H2O, MoSO4·xH2O, Ag2SO4, CdSO4·xH2O, LiCl, NaCl, KCl, TiCl4, VCl3, CrCl3·6H2O, FeCl3·6H2O, CoCl2·6H2O, NiCl2·6H2O, CuCl2·2H2O, ZnCl2, ZrCl4·xH2O, MoCl5·xH2O, AgCl, CdCl2·2H2O, (COOH)3Al·xH2O, (COOH)3Ga·xH2O, (COOH)2Cu·xH2O, (COOH)2Zn·xH2O, LiNO3, one or more thereof.
8. The preparation method according to claim 1, characterized in that: The film is doped with the metal cations; the preparation method further comprises: washing the film in a second solvent.
9. The preparation method according to claim 8, characterized in that: The second solvent comprises one or more of deionized water, chlorobenzene, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide, acetone, acetophenone, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, ethyl ester, pyrrole, butyric acid, and cresol; and / or The washing time is 1s to 600s; and / or After the washing, the film is heated at a temperature of 60° C. to 230° C. for a time of 1 minute to 120 minutes.
10. A film, characterized in that: The invention comprises inorganic particles and metal cations disposed in gaps between the inorganic particles.
11. The film according to claim 10, characterized in that In the film, the molar ratio of the metal cations to the inorganic particles is (1-100):1; and / or The roughness of the film is 0.3nm to 1.32nm; and / or The metal cations are connected to the surface of the inorganic particles, and the connection bonds between the inorganic particles and the metal cations include one or more of ionic bonds, covalent bonds, and metal bonds.
12. A photoelectric device, characterized in that: It comprises a first electrode, a functional layer and a second electrode which are stacked in sequence; the functional layer comprises a film prepared by the preparation method according to any one of claims 1 to 9, or comprises a film according to any one of claims 10 to 11.
13. The optoelectronic device according to claim 12, characterized in that The functional layer includes one or more of a first carrier functional layer, a photoactive layer, and a second carrier functional layer; the first carrier functional layer is arranged between the first electrode and the photoactive layer, and the second carrier functional layer is arranged between the photoactive layer and the second electrode; one or more of the first carrier functional layer, the photoactive layer, and the second carrier functional layer includes a thin film prepared by the preparation method according to any one of claims 1 to 9; The first carrier functional layer is a hole functional layer, and the second carrier functional layer is an electron functional layer; or, the second carrier functional layer is a hole functional layer, and the first carrier functional layer is an electron functional layer.
14. The optoelectronic device according to claim 13, wherein: The first electrode and the second electrode independently include one or more of a metal, a carbon material and a metal oxide; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode in which a metal is arranged between doped or undoped transparent metal oxides, the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, MoO3 and AMO, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or The material of the photoactive layer includes quantum dots and metal cations, or includes luminescent materials, and the luminescent materials include one or more of organic luminescent materials and quantum dots; the organic luminescent materials include 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine iridium(III)], 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine iridium], diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials , DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF materials, polymers containing BN covalent bonding, HLCT materials, Exciplex luminescent materials or more; the quantum dots include single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials or more, the materials of the single structure quantum dots, the core materials of the core-shell structure quantum dots and the shell materials of the core-shell structure quantum dots are independently selected from one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds, The shell layer of the core-shell structure quantum dot is one or more layers; the II-VI group compound includes CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZ nSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound includes one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe;The III-V group compounds include one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compounds include one or more of CuInS2, CuInSe2 and AgInS2; the general structural formula of the perovskite semiconductor material is AMY3, wherein A is Cs; + 、CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, Y is selected from Cl - Br - ,I - One or more of; and / or The material of the electronic functional layer includes N-type semiconductor particles and metal cations, or includes electronic functional materials, wherein the electronic functional materials include first doped metal oxide particles, first non-doped metal oxide particles, IIB-VIA semiconductor materials, IIIA-VA semiconductor materials and IB-IIIA-VIA semiconductor materials, wherein the material of the first non-doped metal oxide particles includes one or more of ZnO, TiO2, SnO2, ZrO2 and Ta2O5, and the metal oxide in the first doped metal oxide particles includes ZnO, Ti O2, SnO2, ZrO2, Ta2O5, Al2O3, the doping element in the first doped metal oxide particles includes one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, Ga, the IIB-VIA semiconductor material includes one or more of ZnS, ZnSe, CdS, the IIIA-VA semiconductor material includes one or more of InP, GaP, the IB-IIIA-VIA semiconductor material includes one or more of CuInS, CuGaS; and / or The material of the hole functional layer includes P-type semiconductor particles and metal cations, or includes hole functional materials, and the hole functional materials include 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N , N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazolyl-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'- dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylenevinylene), poly(phenylenevinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylenevinylene [base], copper phthalocyanine, aromatic tertiary amine, polynuclear aromatic tertiary amine, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraaryl benzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, second doped metal oxide particles, second undoped metal oxide particles, metal sulfide, metal selenide and metal nitride, the metal oxide in the second doped metal oxide particles and the metal oxide in the second undoped metal oxide particles each independently include one or more of MoO3, WO3, NiO, CrO3, CuO, V2O5, the doping element in the second doped metal oxide particles includes one or more of Mo, W, Ni, Cr, Cu, V, the metal sulfide includes one or more of CuS, MoS3, WS3, the metal selenide includes one or more of MoSe3, WSe3, the metal nitride includes P-type gallium nitride; and / or, One or more of the photoactive layer, the hole functional layer and the electron functional layer include metal cations.
15. A display device, characterized in that: The optoelectronic device comprises the optoelectronic device according to any one of claims 11 to 14.
